The Role of Interactive Techniques in the Educational Process - Masharipovna, Rajapova Kumush (European Journal of Life Safety and Stability (2660-9630), 2022)
This article will talk about the role of interactive techniques in the educational process. Therefore, in the course of the lesson, information is also provided on practical and creative work, which is carried out using interactive methods. Opinions were also expressed about the importance of interactive techniques in the cultivation of students ’ speech.